Fluoroquinolones Resistance Among Bacterial Uropathogens In A Tertiary Care Hospital Of Western Nepal - Bhatta, Dharm Raj; Shrestha, Rajani; Hamal, Deependra; HS, Supram; Nayak, Niranjan (Birat Journal of Health Sciences, 2020)
Introduction: Urinary tract infections are one of the most common clinical illnesses in developing countries. Most of the infections are treated empirically due to unavailability of laboratory facilities. Fluoroquinolones are frequently used for empirical treatment of UTIs. Objectives: This study was aimed to determine prevalence and antibiotic resistance pattern of bacterial uropathogens, especially to fluoroquinolones. Methodology: This hospital based cross sectional study was carried out at Manipal Teaching Hospital, Pokhara, Nepal. A total of 2450 mid stream urine samples were included in this study. Isolation, identification and antibiotic susceptibility testing of the isolates was performed by standard microbiological techniques. Results: Significant bacteriuria was detected in 258 (10.5%), insignificant bacteruria in 614 (25%), growth of multiple organisms in 238 (9.7%) while no growth was recorded in 1340 (54.7%) samples. E coli was the commonest isolate followed by Klebsiella species. Fluoroquinolones resistance among Gram negative isolates was high. Most of the Gram negative isolates were susceptible to amikacin, gentamicin, nitrofurantoin and imipenem. Conclusion: High resistance to fluoroquinolones, cotrimoxazole and cephalosporins dictates these to be unsuitable for empirical treatment of UTIs. Amikacin, gentamicin, nitrofurantoin and imipenem were the most effective antibacterials.